Study of ocular surface temperature of normal subjects by textural parameters - Li, Min. (2010)
Infrared (IR) thermography is a technique which can measure Ocular Surface Temperature (OST) without causing trauma on subjects. This project uses a semiauto method to acquire ocular surface temperature from thermal images. Temperature data obtained from the semi-auto method was extracted and analyzed to determine if metabolic rate affects the texture parameters of eye images. In order to gain a proper understanding of the use of IR thermography in ophthalmology, a review of past and current works on ocular thermography is done to determine the factors that affect the OST and also how thermography is used. A study of the eye anatomy and its diseases are reviewed. Statistical tests and texture features are also introduced. The image of the eye is captured by a thermal imaging camera in department of ophthalmology of NUH. Texture parameters data was extracted from the images by semi-auto method which uses an in-house developed algorithm designed in MATLAB. After collecting the data, the statistical tests and texture feature analysis were performed. The data were separated into two controlled groups (normal subjects): the first group consisting of age group younger than 35 (14 to 34 years old) which is “below 35” and the other older than 35 (36 to 76 years old) which is “above 35”.